Burn Survivors' Near-Death Experiences: A Qualitative Examination. (February 2020) - Royse, David; Badger, Karen
Persons who come close to death but survive catastrophic accidents sometimes report very vivid experiences during times when their survival was in doubt, when they were believed to be dead, and during resuscitation efforts. This qualitative study builds upon existing research on near-death experiences (NDEs) by focusing on the oral accounts from a sample of individuals with large and life-threatening burns. The NDE accounts were obtained from burn survivors attending the Phoenix Society's World Burn Congress and are similar to reports by notable researchers (Greyson, 2003 ;Moody, 1975 ;Ring, 1980 ) while reflecting the uniqueness of the individual survivor's experiences. Six major themes are reported. Counselors and health professionals need to be aware of and educated about NDEs as these experiences can have profound effects upon the individual. Patients who have had NDEs may need to discuss them but fear professionals will reject their stories as being crazy.